Anatomical and physiological adaptation of domestic animals to ecosystem constraints: the example of the camel in arid lands (Experimental biology, 2015)
The local breed or species used as farm animals are generally well adapted to their environment. This adaptation is based on three main components: the ability to support thermal stress by a specific thermoregulation process, the management of the seasonal and/or inter-annual fluctuation in the feeding resources, and the resistance to diseases linked to the local environment. These three components are discussed with special emphasis on the camel model, one of the more adapted species in arid lands.
Keywords: Adaptation; thermal regulation; fat storage management; disease resistance; camel